The olive oil and cotton lint sectors in the European Union - Gadanakis, Yiorgos; Clapan, Carmen; Drakos, Periklis; Baourakis, George (My University, 2006)
This paper examines and analyzes the impacts of the reformed CAP as well as the decisions of the new round of negotiations for the olive oil and cotton sectors in the European Union. The aim of this study is to estimate the changes in supply (agricultural supply plus intermediate demand and final production), demand (consumption), price and stock formation (import, export, beginning and ending stocks, national price formation) for both the olive oil and cotton sectors. The model designed for this purpose is partial equilibrium and policy oriented. The objectives of this model are to estimate changes in the production and consumption of the two products concerned, to determine how the reformed Common Agricultural Policy (CAP) and the new round of negotiations of the World Trade Organization (WTO) affect these two sectors, to analyze the evolution of export and import volumes, and finally to determine how this evolution will influence the welfare situation of the olive oil and cotton sectors.
Keywords: Olive oil; Cotton; socio economic effects; partial equilibrium model; dynamic; multi market; policy oriented simulation model